2017
DOI: 10.1016/j.bcp.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

RhoA S-nitrosylation as a regulatory mechanism influencing endothelial barrier function in response to G + -bacterial toxins

Abstract: Disruption of the endothelial barrier in response to Gram positive (G+) bacterial toxins is a major complication of acute lung injury (ALI) and can be further aggravated by antibiotics which stimulate toxin release. The integrity of the pulmonary endothelial barrier is mediated by the balance of disruptive forces such as the small GTPase RhoA, and protective forces including endothelium-derived nitric oxide (NO). How NO protects against the barrier dysfunction is incompletely understood and our goal was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 53 publications
(77 reference statements)
2
16
0
Order By: Relevance
“…NMR and X-ray crystal structures for Rho family GTPases propose that the Cys18 thiol in the GXXXXGK(S/T)C motif is accessible for solvent and suggest reactive oxygen species and reactive nitrogen species possibly target the Cys18 thiol [ [35] , [36] , [37] ]. Further, we have shown that S-nitrosylation of RhoA attenuates the activity of RhoA[ 38 ]. The effect of S-nitrosylation on Rac1 is unresolved but we speculate that as nitration activates while S-nitrosylation inhibits RhoA that S-nitrosylation may stimulate Rac1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…NMR and X-ray crystal structures for Rho family GTPases propose that the Cys18 thiol in the GXXXXGK(S/T)C motif is accessible for solvent and suggest reactive oxygen species and reactive nitrogen species possibly target the Cys18 thiol [ [35] , [36] , [37] ]. Further, we have shown that S-nitrosylation of RhoA attenuates the activity of RhoA[ 38 ]. The effect of S-nitrosylation on Rac1 is unresolved but we speculate that as nitration activates while S-nitrosylation inhibits RhoA that S-nitrosylation may stimulate Rac1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumolysin has been well documented to disrupt barrier function in HLMVEC and increase endothelial permeability ( 12 , 13 , 41 , 42 ). To determine the effect of Hsp70 on barrier function, HLMVECs were transduced with adenoviruses encoding Hsp70 (pAd Hsp70-GFP, 60MOI) or GFP (Control, 60MOI) overnight and then transferred to an ECIS plate.…”
Section: Resultsmentioning
confidence: 99%
“…Pneumolysin and other cholesterol-dependent pore-forming cytolysins from G + -bacteria such as listeriolysin O have been shown to form plasma membrane pores that stimulate calcium entry and promote disruption of the endothelial barrier ( 12 , 13 , 41 , 42 , 47 ). Multiple mechanisms have been proposed, including activation of PKC, disruption of NO signaling, arginase induction, and inhibition of ENaC.…”
Section: Discussionmentioning
confidence: 99%
“…A number of molecular mechanisms have been identified in VILI including Ca 2+ dependent pathways, activation of protein kinases (including PKC and Rho kinase) and the modulation of eNOS activity [ 13 ], and an excessive ROS generation [ [14] , [15] , [16] , [17] ]. Interestingly, our recent study demonstrated that PKC-dependent phosphorylation of eNOS T495 leads to enzyme uncoupling, increased peroxynitrite production, and barrier disruption [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations also revealed that PKC dependent phosphorylation of eNOS at Thr495, increased mitochondrial derived ROS [ 19 ]. It is widely accepted that calcium entry into EC is necessary for barrier disruption [ 14 ]. As eNOS uncoupling can be catalyzed by PKCα [ 16 ] this suggest a link between increases in intracellular [Ca 2+ ] and eNOS uncoupling and the EC barrier permeability associated with VILI.…”
Section: Introductionmentioning
confidence: 99%